2020
DOI: 10.1177/0306624x20928023
|View full text |Cite
|
Sign up to set email alerts
|

Attempted and Completed Parricides in South Africa, 1990–2019

Abstract: Previous studies of parricide have been carried out predominantly in a Western context, in North America, Australia, and Western Europe. To date, only a handful of studies in parricide have been conducted in continental Africa. Previous studies in Ghana and Zimbabwe note that there may be culture-specific ways in which parricides may be shaped by the norms and cultural beliefs systems within those respective countries. Missing from the literature is an examination of parricides in South Africa. Using newspaper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Although an attempt was made to capture as much information as possible, the study was limited by what was reported in the newspapers and court documents. Nevertheless, content analysis of newspaper articles gives the reader a glimpse on real life social occurrences and the descriptions in these documents can be analysed as units of behavioural analysis (Moen & Shon, 2021).…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Although an attempt was made to capture as much information as possible, the study was limited by what was reported in the newspapers and court documents. Nevertheless, content analysis of newspaper articles gives the reader a glimpse on real life social occurrences and the descriptions in these documents can be analysed as units of behavioural analysis (Moen & Shon, 2021).…”
Section: Limitations Of the Studymentioning
confidence: 99%